Interleukin-18 serum levels in inflammatory bowel diseases: correlation with disease activity and inflammatory markers - Haas, Stephan; Abbatista, Monica; Brade, Joachim; Singer, Manfred V.; Böcker, Ulrich (Swiss medical weekly, 2009)
BACKGROUND: An imbalance of cytokines is believed to contribute to the immunopathogenesis of inflammatory bowel diseases (IBD). Serum cytokine levels may correlate with disease activity and acute phase reactivity. - AIM: To determine the correlation of systemic interleukin-18 (IL-18) levels with disease activity and other markers of inflammation using a crosssectional pilot study in outpatients with IBD. - METHODS: Peripheral venous blood was obtained from 84 patients with Crohn's disease (CD) and from 46 patients with ulcerative colitis (UC). Serum levels of C-reactive protein (CRP), IL-8, IFN-gamma, IL-12p70 and IL-18 were assessed by ELISA. Disease activity was expressed by the Crohn's Disease Activity Index (CDAI) and the Clinical Activity Index (CAI), respectively. Statistical analysis comprised correlation coefficients and linear regression analysis. - RESULTS: In CD IL-18 and other cytokine concentrations, CRP levels, leukocyte and platelet counts did not correlate with the CDAI. However, IL-18 as well as IL-8 and platelets positively correlated with CRP levels (p <0.001), while IFN-gamma and IL-12p70 did not. In contrast, in UC only the CAI and CRP levels showed a significant positive correlation. COMCLUSIONS: In CD IL-18 lacks significant correlation with the CDAI, as do serum acute phase protein and other cytokine markers of inflammation. As opposed to UC, IL-18 and IL-8 may, however, serve as indicators of acute phase reactivity in CD and should be explored in a larger study.